Difficulties diagnosing spinal subdural hemorrhage in a hypo-coagulated patient due to simultaneous symptomatic subdural cranial hemorrhage - Mascarenhas, L (2012)
A hypo-coagulated 58-year-old female complained of headaches right after being exposed to the first pressure waves generated during an exhibition of fireworks. The day after she presented with seizures and the CT scan showed subdural hemorrhage over the left frontoparietal sulci. Eight hours after admission she disclosed left lower limb hypo-esthesia, i.e. a finding not attributable to the cranial hemorrhage. Four hours later sphincter dysfunction and paraparesis were also present with a left predominance. This was due to a T12-L1 subdural extramedullary hemorrhage. The patient was operated and showed a favorable outcome. Hypo-coagulated patients with cranial hemorrhage require prolonged surveillance and may harbor spinal hemorrhage as well. This rare combination can be unsuspected in view of the evident cranial event, and may cause severe neurological deficits if not detected.